Clinical Presentation of Left Atrial Myxoma in Relation to Anatomic and Pathologic Type - Rahman, SM Mahbubur; Kibria, M Golam; Rahim, AM Asif; Hosain, Nazmul; Quashem, M Abul (Cardiovascular Journal, 2015)
Background: Atrial myxoma is the most common benign cardiac neoplasm. Most of the case series have focused on the variable clinical presentation of myxoma rather than its gross and microscopic features. The objective of our study was to evaluate prevalence of different morphologic types of myxoma and to correlate with their clinical presentations. Methods: 68 patients were included in the study. The study population was divided into two groups- Group-A (n-18) patients having soft (papillary) tumor in the left atrium, Group B (n=50) patients having solid tumor in the left atrium. Results: 88.3% patients suffered illness more than 12 months. 92% of the solid myxomas were located in the septal wall compared to 55.6% of the papillary myxomas (p = 0.031), while one-third (33.3%) the papillary tumors were found in the left atrial free wall compared to only 4% of the solid myxomas (p = 0.048). Fever, congestive heart failure and dyspnoea were significantly predominant in patients with solid myxomas (72% vs. 44.4%, p = 0.036; 92% vs. 22.2%, p < 0.001 and 88% vs. 55.6%, p = 0.010 respectively). Atrial fibrillation and neurologic manifestations were more frequently encountered in the papillary myxoma group. No statistically significant difference was found between the groups (p>0.05) by postoperative complication during in hospital follow up but one mortality in each group. Conclusion: Our findings lend support to the view that different gross left atrial Myxoma tumor types and tumor location predict presentation. Cardiovasc. j. 2015; 8(1): 19-22